Mastering the VC Game: A Venture Capital Insider Reveals How to Get from Start-up to IPO on Your Terms - Jeffrey Bussgang (USA Portfolio/Penguin, 2011)
"Read this book right now so you can look your potential VC in the eye with confidence." -David Meerman Scott, author of The New Rules of Marketing & PR Finding the right venture capitalist to back your start-up is a challenge. Even if you manage to get backing, you want your VC to be a partner, not some dictator who will undermine your vision and take control of your life's work. Jeffrey Bussgang is one of a very few people who have played on both sides of this high-stakes game. Now he draws on his unique perspective to offer high-level insights, colorful stories, and practical advice gathered from his own experience as well as from interviews with dozens of the most successful entrepreneurs and VCs. He reveals how to get noticed, perfect a pitch, and negotiate a partnership that works for everyone.
Keywords: Venture capital; Finance; Nonfiction